272 Point-of-care testing in paediatric settings in the UK and Ireland: a cross-sectional study. (17th August 2022) - Pandey, Meenu; Lyttle, Mark; Cathie, Katrina; Munro, Alasdair; Waterfield, Thomas; Roland, Damian
Abstract : Aims: Point-of-care testing (POCT) is diagnostic testing performed at or near to the site of the patient. It has the potential to provide rapid and accurate results that can help deliver optimal patient care in emergency and acute care settings, help prevent and resolve department crowding and protracted discharge times, in addition to enhanced patient satisfaction. The primary aim of this study was to describe POCT in its current use in acute paediatric settings across the UK and Ireland. Secondary objectives were to examine implementation, maintenance, funding, governance and further opinions on the introduction of new POCT including obstacles and enablers. Methods: A cross-sectional online survey study of POCT use was conducted between 6 th January and 2 nd February 2020 on behalf of two United Kingdom (UK) and Ireland-based paediatric research networks (Paediatric Emergency Research UK and Ireland, and General and Adolescent Paediatric Research UK and Ireland). This was reported in accordance with the Checklist for Reporting Results of Internet E-Surveys (CHERRIES). As this survey study contained no patient level data, ethical approval was unnecessary according to the Health Research Authority framework decision tool. Results: In total 91/109 (83.5%) sites responded, with some respondents providing details for multiple units on their site based on network membership (139 units in total). The most commonly performed POCT were blood sugar (98.6%), urinalysis (96.4%) and blood gas analysis (95%). The use of POCT for Influenza/Respiratory Syncytial Virus (RSV) (32.4%, 29.5%), C-Reactive Protein (CRP) (9.4%), Procalcitonin (PCT) (1.4%) and Group A Streptococcus (3.6%) was markedly low. POCTs were mostly performed by nurses (33.1%) followed by Emergency Nurse Practitioners (ENP)/Advanced Nurse Practitioners (ANP) (20.4%) and junior doctors (18.1%). POCT were mostly acted upon by senior non-consultants (23.8%), consultants (23.8%) and junior trainees (22.7%). POCT governance was mainly carried on as a joint responsibility between clinical and laboratory teams (61.7%), followed by laboratory teams taking full responsibility (33.2%). The POCT most likely to come under shared responsibility were urinary human Chorionic Gonadotropin (hCG) (70.7%), urinalysis (70.2%), blood sugar (69.7%) and blood ketones (68.5%). POCT run on units with more complexity (for example, blood gases) were primarily managed by laboratory teams (53.5%, ). The most common method of data storage was as handwritten notes in clinical records (35.6%), followed by printouts (26.6%) and manual entry (21.6%). Automatic uploading to electronic systems occurred in 15.8% of responses. The most common obstacles to the use of POCT included funding difficulties (45.6%), lack of evidence (20.9%) and issues with POCT governance (12.7%). POCT were typically funded as part of an ongoing service with sustainable long-term funding (82.7%), followed by temporary funding as a part of a service evaluation (10.2%), or charitable funding and/or donations (5.1%). Conclusion: This survey demonstrates significant consensus in POCT practice in the UK and Ireland, but also highlights specific inequity in newer biomarkers, some which do not have support from national guidance. A clear strategy to overcome the key obstacles of funding, evidence base, and standardising variation will be essential if there is a drive toward increasing implementation of POCT.